The Male Gaze and Online Sports Punditry: Reactions to the Ines Sainz Controversy on the Sports Blogosphere. (February 2015) - Merrill, Kenneth; Bryant, Aidan; Dolan, Emily; Chang, Siying
On September 11, 2010, Ines Sainz, a sports reporter for Mexican television network TV Azteca, was allegedly harassed by members of the New York Jets football team. Controversy erupted around the role of women in sports broadcasting and the myriad attendant dimensions involved, including issues of credibility, dominant beauty ideals, and the male gaze, among others. This study assesses how sports blogs covered the controversy, using a combination of in-depth interviewing and textual analysis of four popular sports blogs. The analysis revealed that the blogs constructed an atmosphere that exposed attitudes of objectification, Sainz's perceived lack of credibility, and the sexual economy of sports blogs.